The aortic-femoral arterial stiffness gradient is blood pressure independent in older adults: the atherosclerosis risk in communities (ARIC) study. Issue 12 (2nd December 2021) - Stone, Keeron; Fryer, Simon; Faulkner, James; Meyer, Michelle L.; Heffernan, Kevin; Kucharska-Newton, Anna; Zieff, Gabriel; Paterson, Craig; Matsushita, Kunihiro; Hughes, Timothy M.; Tanaka, Hirofumi; Stoner, Lee
Abstract : Supplemental Digital Content is available in the text Abstract : Background: Aortic arterial stiffness is a strong independent predictor of cardiovascular disease (CVD); however, its dependence on mean arterial pressure (MAP) limits its clinical utility. The aortic-femoral arterial stiffness gradient (af-SG), a novel marker of CVD risk, may be a promising alternative, but its dependence on MAP is not known. The aim of this study was to determine the relationship between MAP and the af-SG in healthy older adults and those with established disease, including hypertension and diabetes. Method: We evaluated the dependency of the af-SG on MAP in healthy older adults ( n = 694, aged 74 ± 5 years), and adults with hypertension ( n = 2040, aged 76 ± 5 years), and diabetes ( n = 1405, aged 75 ± 5 years) as part of the community-based Atherosclerosis Risk in Communities (ARIC) Study. Carotid-femoral pulse-wave velocity (cfPWV), femoral-ankle PWV (faPWV) and blood pressure were measured using standardized protocols. The af-SG was calculated as faPWV divided by cfPWV. Multivariable regression analysis was performed to test the independent association of MAP with af-SG, with adjustments for known confounders, including age, sex, BMI, blood glucose and heart rate. Results: There was no significant relationship between the af-SG and MAP in healthy (β = 0.002, P = 0.301), hypertension (β = −0.001, P = 0.298) or diabetes (β = −0.001, P = 0.063) population groups, with MAP explaining less than 0.1, less than 0.1 and 0.2% of the variance in the af-SG, respectively. Conclusion: These findings suggest that the af-SG may be regarded as a MAP independent index of arterial health and CVD risk in older adults.